The Effect of Employee Engagement, Rewards, and Leadership Style on Turnover Intention at Ijen View Bondowoso Hotel - Pratiwi Yenitasari; Sampeadi Sampeadi; Wiji Utami (UPT Penerbitan Universitas Jember, 2020)
The objective of this research is to analyze the effect of employee engagement, rewards, and leadership style on employee turnover intention at Ijen View Bondowoso Hotel. This research is an explanatory research. The sample used in this research consisted of 98 employees. The analysis method used was multple linear regression. The results showed that employee engagement, rewards, and leadership style have a significant and negative effect on turnover intention. These findings imply that the higher employee engagement, rewards, and leadership style, the lower the turnover intention rate.